THE EFFECTIVENESS OF GREEN BETEL LEAF (Piper betle L.) DECOCTION AS ANTIBACTERIA Escherichia coli AND Staphylococcus aureus - Enong Liha (PHARMACON, 2023)
Piper betle as a folk remedy has been used to inhibit the growth of bacteria, by making various ways one of which is decoction. The purpose of this study was to determine the effectiveness of green betel leaf decoction as an antibacterial of Escherichia coli and Staphylococcus aureus. The samples used were green betel leaf decoction with a concentration of 17%, 34%, 51%, 68%, Amoxicillin, and Aquadest. Antibacterial testing using the Kirby & Bauer diffusion method with four repetitions. The results showed that the average inhibition zone of each stew concentration in E.coli bacteria was classified as weak (≤5 mm), namely 17% by 2,12 mm; 34% by 1,00 mm; 51% by 1,37 mm; and 68% by 3,50 mm. The average inhibition zone of each boiled concentration in S.aureus bacteria is classified as weak (≤5 mm) to moderate (5-10 mm) which is 17% by 7,87 mm; 34% by 4,00 mm; 51% by 4,97 mm; and 68% by 4,87 mm. The conclusion is that a decoction of green betel leaves is less effective in inhibiting the growth of E.coli and S.aureus bacteria.